CD4+ virtual memory: Antigen-inexperienced T cells reside in the naïve, regulatory, and memory T cell compartments at similar frequencies, implications for autoimmunity. (February 2017) - Marusina, Alina I.; Ono, Yoko; Merleev, Alexander A.; Shimoda, Michiko; Ogawa, Hiromi; Wang, Elizabeth A.; Kondo, Kayo; Olney, Laura; Luxardi, Guillaume; Miyamura, Yoshinori; Yilma, Tilahun D.; Villalobos, Itzel Bustos; et al.
Abstract: It is widely accepted that central and effector memory CD4 + T cells originate from naïve T cells after they have encountered their cognate antigen in the setting of appropriate co-stimulation. However, if this were true the diversity of T cell receptor (TCR) sequences within the naïve T cell compartment should be far greater than that of the memory T cell compartment, which is not supported by TCR sequencing data. Here we demonstrate that aged mice with far fewer naïve T cells, respond to the model antigen, hen eggwhite lysozyme (HEL), by utilizing the same TCR sequence as their younger counterparts. CD4 + T cell repertoire analysis of highly purified T cell populations from naive animals revealed that the HEL-specific clones displayed effector and central "memory" cell surface phenotypes even prior to having encountered their cognate antigen. Furthermore, HEL-inexperienced CD4 + T cells were found to reside within the naïve, regulatory, central memory, and effector memory T cell populations at similar frequencies and the majority of the CD4 + T cells within the regulatory and memory populations were unexpanded. These findings support a new paradigm for CD4 + T cell maturation in which a specific clone can undergo a differentiation process to exhibit a "memory" or regulatory phenotype without having undergone a clonal expansion event. It also demonstrates that a foreign-specific T cell is just as likely to reside within the regulatory T cell compartment as it would the naïve compartment, arguing against the specificity of the regulatory T cell compartment being skewed towards self-reactive T cell clones. Finally, we demonstrate that the same set of foreign and autoreactive CD4 + T cell clones are repetitively generated throughout adulthood. The latter observation argues against T cell-depleting strategies or autologous stem cell transplantation as therapies for autoimmunity-as the immune system has the ability to regenerate pathogenic clones. Graphical abstract: Highlights: Antigen-inexperienced CD4 + T cells comprise a portion of the memory repertoire. CD4 + T cells can display a memory phenotype without clonal expansion to an antigen. Our study supports the existence of CD4 + virtual memory T cells. These findings posit a new paradigm for T cell maturation.